UV Spectrophotometric Methods for the Determination of Lercanidipine and Isradipine in Bulk and Pharmaceutical Formulations - Nageswara Rao, R.; Nagaraju, P.; Srinivasulu, C.; Radhakrishnamurthy, P.; Sireesha, D.; Uday Bhaskar, S. (Asian Journal of Chemistry, 2016)
Simple and sensitive UV spectrophotometric methods have been developed for the determination of two anti-hypertensive drugs, namely, lercanidipine and isradipine in bulk and their formulations. Both the drugs were taken in methanol solution and maximum absorbance was observed at 236 nm and 327 nm respectively. Beer’s law was obeyed in the concentration of 2–10 μg/mL for lercanidipine and 2–10 μg/mL for isradipine. There is no interference from any common pharmaceutical additives and diluents.